Tasawuf dan Filsafat Islam sebagai Pilar Spiritualitas Umat Muslim: Tafsir Ontologis atas Eksistensi Manusia - Ghozali Ghozali; Muhammad Asrori (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Islamic philosophy and Sufism have long been important in shaping thought and spirituality in Islamic civilization. Although they have different focuses, both have contributed significantly to the formation of a rich and meaningful outlook on life for Muslims. This study focuses on a profound ontological interpretation of human existence by integrating the spiritual dimension of Sufism and the rational approach of Islamic philosophy. Sufism emphasizes the purification of the soul (tazkiyah al-nafs) and the attainment of makrifatullah (knowledge of God), while Islamic philosophy provides a conceptual foundation through a critical study of human existence and nature. This study uses qualitative methods with descriptive analysis of classical and contemporary literature, through sources from Sufism books, historical books, and various other relevant journals. This study highlights the relevance of Sufism concepts such as fana' (loss of ego) and baqa' (permanence) as well as Islamic philosophical theories about wujud (existence) and essence in the context of contemporary life. The results of this study show that the synergy between Sufism and philosophy is able to provide holistic guidance for building a deep, solid, and relevant spirituality for religious communities amidst the challenges of this contemporary era.   Keywords: Sufism, Islamic Philosophy, Ontology, Human Existence